Implementation the Fourth Character Code of Insulin Dependent Diabetes Mellitus (IDDM) Diagnosis Based International Statistical Classification of Diseases and Related Health Problems - Linda Widyaningrum; Nor Azlinah Md Lazam; Tominanto Tominanto; Dona Yanuar Agus Santoso (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Coding is the assignment of codes by using letters in numbers that represent data components. Activities and actions as well as diagnoses contained in the medical record must be coded and then indexed to facilitate services in presenting information to support the functions of planning, management and research in the health sector. This study aims to determine the application of the 4th character code to the diagnosis of Insulin Dependent Diabetes Mellitus (IDDM) based on ICD 10 in inpatient medical records at RSAU dr Siswanto Lanud Adi Soemarmo in 2020. The research method uses descriptive. The approach used is retrospective with observation and interview data collection. The sample used was 117 inpatient medical record documents with a diagnosis of Insulin Dependent Diabetes Mellitus (IDDM) with a sampling technique using saturated samples.The procedure for implementing the coding is not yet in accordance with the SPO and the SPO for the application of the 4th character code does not yet exist. The accuracy of the application of the 4th character code in the diagnosis of Insulin Dependent Diabetes Mellitus (IDDM) was 57% (67 documents) and 43% (50 documents) incorrectly due to an error in selecting the 4th character code. The factors causing the 4th character code inaccuracy based on ICD 10, namely medical personnel factors and medical record personnel (coder). Researchers suggest that hospitals should socialize to medical personnel about writing a diagnosis, this will minimize errors in the 4th character code. Coder officers should be more careful in coding and check again on ICD 10 volume 1 to provide the right code.